Crustal Structure and Anisotropy in the Lower Yangtze Region and its Metallogenic Implications - Han, Rubing; Yang, Dinghui; Li, Qiusheng; Chen, Hao; Zhang, Hongshuang; Ye, Zhuo; Cheng, Yongzhi; Fu, Wei (Frontiers in Earth Science, 2022)
In this study, we performed receiver function profiling and fitted harmonic functions to the arrival time variations of Pms phases to calculate the crustal seismic anisotropy with delay time and fast polarization direction, using broadband seismic data obtained from 55 temporary stations in two linear profiles and 39 stations in the Lower Yangtze and adjacent region. Moreover, we determined the crustal thickness and Poisson’s ratio using a novel H-κ-c stacking method. Our results revealed that the Middle-Lower Yangtze Metallogenic Belt and the north east section of the Qinzhou-Hangzhou Metallogenic Belt are characterized by Moho upliftment (< 32 km), a relatively high Poisson’s ratio (> 0.26), local lithospheric thinning (< 70 km), and a pattern of deep faults that connect the crust and asthenosphere and serve as conduits for magma upwelling. The NE-SW fast polarization direction was consistent with the SKS splitting results, and the average delay time was 0.45s. Moreover, underplating of deep magma and upwelling along the weak zone caused local Moho uplift and ductile shear of the lower crust, resulting in the directional arrangement of amphibole and other minerals, which may be the controlling mechanism for the crustal anisotropy in the study area. The variations in crustal structure and anisotropy characteristics indicated that in the context of the northeastern Paleo-Pacific plate subduction, the existence of weak lithospheric zones and the northeastern asthenospheric flow are important conditions for metal supernormal enrichment in the Lower Yangtze region.